Pengaruh Penerapan Multimedia Camtasia Studio dan Media Power Point Terhadap Aktivitas dan Hasil Belajar Siswa Pada Materi Struktur Atom - Husuwatul Masyithah; Zainuddin Muchtar; Mahmud Mahmud (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This research aims to know the effect of application camtasia studio multimedia and power-point media toward activities and student learning outcomes in the atomic structure topic. The population in this research were all of tenth grade students of SMA Swasta Ar Rahman Medan as much as 2 classes of 60 people, divided into two classes of samples with total sampling. The research data were collected from the sample is in the form of student learning activity data derived from observation and questionnaire, and student learning outcomes obtained from tests of learning outcomes in the form of multiple choice of 20 questions with a reliability of 0.832 (very high). Tests have been conducted in the form requirements of normality and homogeneity test, the result that normal and homogeneous data. The hypothesis was tested with General Linear Model (GLM) at a significance level of 0.05 using SPSS 21 for windows. Based on data analysis and hypothesis testing are carried out found that: (1) There is a significant difference from the application of Camtasia studio multimedia and power-point toward the learning outcomes of students in the atomic structure topic, which is shown by sig. (P) 0.026 and tcount (2,291) ; (2) There are differences in students' learning activities of the application Camtasia studio multimedia and power-point media in the atomic structure topic, which is shown by sig. (P) 0,000 and mean of experiment-1 (77,69) > mean of experiment-2 (74,35); (3) There was a significant interaction between the media applied learning with students learning activities in influencing student learning outcomes in the atomic structure topic, which is shown by sig. (P) 0,000.Keywords: camtasia studio multimedia, power point media, student activities, learning outcomes, atomic structure